Complete nucleotide sequences of the coat protein messenger RNAs of brome mosaic virus and cowpea chlorotic mottle virus. - Dasgupta, R (1982)
The nucleotide sequences of the subgenomic coat protein messengers (RNA4's) of two related bromoviruses, brome mosaic virus (BMV) and cowpea chlorotic mottle virus (CCMV), have been determined by direct RNA and CDNA sequencing without cloning. BMV RNA4 is 876 b long including a 5' noncoding region of nine nucleotides and a 3' noncoding region of 300 nucleotides. CCMV RNA 4 is 824 b long, including a 5' noncoding region of 10 nucleotides and a 3' noncoding region of 244 nucleotides. The encoded coat proteins are similar in length (188 amino acids for BMV and 189 amino acids for CCMV) and display about 70% homology in their amino acid sequences. Length difference between the two RNAs is due mostly to a single deletion, in CCMV with respect to BMV, of about 57 b immediately following the coding region. Allowing for this deletion the RNAs are indicate that mutations leading to divergence were constrained in the coding region primarily by the requirement of maintaining a favorable coat protein structure and in the 3' noncoding region primarily by the requirement of maintaining a favorable RNA spatial configuration.